Вопрос о динамике лексики русского языка в конце ХХ—начале ХХI вв. на страницах журнала „Studia Rossica Posnaniensia” - Tetiana Kosmeda (Studia Rossica Posnaniensia)
In the course of analysing publications from the journal “Studia Rossica Posnaniensia”, devoted to the problem of Russian vocabulary mobility during the last 20–30 years, it was concluded that Russian vocabulary is actively enriched by borrowings and internationalisms, in particular: the formation of new words (morphological way),  in the sphere of personal naming, broadening the lexico-semantic group of adverbs. Onomastics has been actively developed; set word meanings have extended and transformed; among newly formed words there are many that express emotionally evaluative relations; finally, the stylistic status of words is being changed, with the corpus of profanities enriched.